PENGARUH CORPORATE SOCIAL RESPONSIBILITY PADA KINERJA KEUANGAN PERUSAHAAN DAN IMPLIKASINYA TERHADAP NILAI PERUAHAAN - Prasetya Nugraha, Dinar; Meiranto, Wahyu (Faculty of Economics and Business Diponegoro University, 2014)
This study aims to determine the effect of Corporate Social Responsibility on thecompany's performance and its implications for the value of the company. Intervening variable using the company's performance in the ROA and ROE proxy.The population in this study are listed companies in Indonesia Stock Exchange2010-2013. Sampling was done by purposive sampling technique. Data analysis techniques performed by regression analysis and path analysis.Based on the analysis conducted found that the results of the Corporate Social Responsibility positive effect on ROE but had no effect on ROA. Corporate social responsibility has positive effect on firm value. Financial Performance are proxied by ROE can mediate relations between Corporate social responsibility with the company's financial performance but are proxied by ROA can not mediate relations between Corporate social responsibility with corporate values